SANCTIONS FOR ADULTERER: A COMPARATIVE STUDY OF ACEH'S QANUN AND SELANGOR'S ENACTMENT - Cempaka Sari Harahap; Ali Abu Bakar; Badrul Munir (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2018)
Penalties for adulterers have been regulated by law in a number of countries with their respective sanctions. One such arrangement is through Aceh Qanun No. 6 of 2014 concerning the Law of Jinayat and the Enactment of the Syariah Law of Selangor No. 9 of 1995 Sex. 25. But the penalties set out in the Aceh Qanun are different from the punishment of adultery perpetrators regulated in Selangor State Sharia Youth Enactments, therefore this study aims to find out what penalties are contained in the Aceh Qanun and the Selangor State Islamic Law, and what lies behind this difference. to get the answer to the problem of punishment for adulterers, the writer uses descriptive-comparative method. This research is categorized as library research. Punishment regulated in Qanun No. 6 of 2014 concerning jinayat law is a lash of 100 (one hundred) times without distinguishing between the muhsan and ghair muhsan, whereas in the Enakmen regulates adultery sanctions on three categories: fines, imprisonment and caning (sebat), this sentence is determined in the religious court (Syar Court 'iyah in Aceh or the Syariah Court in Selangor). The Selangor State Islamic Law Enactment regulates more criminal acts but the provisions of the sanctions are more severe in the Aceh Qanun. This is because in Selangor in the determination of penalties for perpetrators of crimes in Malaysia using Ta'zir's punishment and more looking at the benefits and local wisdom of Selangor State. While the Qanun is based on the punishment of hudud, which hudud is a punishment that has been determined the form and level by Allah SWT. In the author's opinion, punishment that is more in line with the sanctions of adultery is a punishment that is regulated in the Aceh Qanun because according to the provisions set out in the text namely 100 (one hundred) lashes, although it does not distinguish between muhsan adulterers and adulterers Ghair muhsan. Abstrak: Hukuman bagi penzina telah diatur oleh hukum di sejumlah negara dengan sanksi masing-masing. Salah satu pengaturan tersebut adalah melalui Qanun Aceh No. 6 tahun 2014 tentang Hukum Jinayat dan Penetapan Hukum Syariah Selangor No. 9 tahun 1995 pasal 25. Tetapi hukuman yang ditetapkan dalam Qanun Aceh berbeda dengan hukuman terhadap penzina yang diatur dalam Undang-Undang Selangor State Sharia Youth Enactments. Penelitian ini termasuk penelitian kepustakaan. Hukuman yang diatur dalam Qanun No. 6 tahun 2014 tentang hukum jinayat adalah 100 kali cambuk tanpa membedakan antara muhsan dan ghair muhsan, sedangkan dalam State Sharia Youth Enactments sanksi perzinahan terbagi menjadi tiga kategori: denda, hukuman penjara dan hukuman cambuk, hukuman ini ditentukan di pengadilan agama (Pengadilan Syar'iyah di Aceh atau Pengadilan Syariah di Selangor). Qanun didasarkan pada hukuman hudud, dimana hudud merupakan hukuman yang telah ditentukan bentuk dan tingkatannya oleh Allah SWT. Hukuman yang lebih sesuai untuk sanksi perzinaan adalah hukuman yang diatur dalam Qanun Aceh karena sesuai ketentuan yang diatur dalam Al-Quran yaitu 100 (seratus) cambuk. Kata kunci: Hukuman bagi pezina, Hukuman, Hukum Jinayat Islam